An ABAQUS plugin for rotary draw bending of tight fit pipes. (December 2022) - Naderi, Gholamali; Dibajian, Seyed Houssain; Torshizi, Seyed Ebrahim Moussavi; Masoumian, Amirreza; Stockinger, Martin
Abstract: This paper investigates the bending of a Tight Fit Pipe (TFP). It is a double-walled pipe with a corrosion-resistant alloy (CRA) liner fitted inside a carbon steel outer pipe through thermal-hydraulic production. Due to the effects of various variables, such as the process of production of a double-walled pipe, the initial imperfections in the inner pipe, and the mandrel location in rotary draw bending (RDB) without defects, it is not easy to study TFP bending. For efficient process modeling, a new plugin is developed. With this plugin, the production and bending are easily simulated and present the final bending quality (separation, wrinkling, ovality, and springback) in a few diagrams wholly and concisely. A stress histogram is introduced to quantify the investigation of separation between pipes and wrinkling. The plugin evaluates the ovality diagram, and the amount of springback is presented directly. Then the production and bending processes are performed experimentally, and the capability of the plugin is investigated. Due to the adaptation of residual stress in the production process and the plugin results, the simulation accuracy in the production process is confirmed. Then the comparison of wrinkling at the end of the process shows good agreement between the results of the presented plugin and the experimental results. Abstract : A new abaqus plugin is presented to simulated the rotary draw bending of Tight Fit Pipe. The imperfections which are mentioned in various articles are integrated and simulated in this plugin. In ABAQUS GUI, it is not possible to simulate these imperfections. In the presented plugin, the post processing is done for faster and more accurate evaluation of bending quality. A contact pressure histogram is introduced to quantify separation between inner and outer pipes and wrinkling. The ovality diagram and the amount of springback are evaluated by the plugin and are presented directly.